Effectiveness of ASA for VTE Prophylaxis in Arthroscopic Rotator Cuff Repair. Issue 7 (30th July 2018) - Austin, Luke; Wowkanech, Charles Dante; Cypel, Bret; Alyea, Eric Gordon; Gaston, Tara; Pontes, Manuel; Williams, Gerald R.
Objectives: Venous thromboembolic disease (VTED) is a rare complication following arthroscopic rotator cuff repair (RCR). Historical rates of symptomatic VTED after arthroscopic shoulder surgery, DVT and PE, are 0.26%, and 0.01-0.21%, respectively. At present, the American Academy of Orthopaedic Surgeons (AAOS) and American College of Chest Physicians (ACCP) have no prophylaxis guidelines specific to shoulder arthroscopy. Despite this, many surgeons prescribe Aspirin (ASA) for chemical prophylaxis following RCR. The efficacy of ASA as a thromboprophylaxis after shoulder arthroscopy is unknown, but there are risks associated with its' use. The purpose of this study is to evaluate the effectiveness of chemical prophylaxis (ASA) and mechanical prophylaxis vs. mechanical prophylaxis alone in preventing VTED following RCR. Methods: A total of 914 patients underwent RCR between the months of January 2010 and January 2015. A retrospective case control study was performed. The control group (n=484) consisted of patients treated with perioperative mechanical VTED prophylaxis (compression boots) and early mobilization. The study group (n=430) also utilized perioperative mechanical prophylaxis and early mobilization, and added chemical prophylaxis (ASA 81 mg daily) for four weeks after surgery. The primary outcome was symptomatic VTED (DVT/PE). Chart records were collected and evaluated for six months after surgery. Patient demographics and other surgical complications were also analyzed. Results: A total of 7 VTED events occurred during the study period, 6 DVTs and 1 PE. The total rate of VTED was 0.88%, DVT was 0.77%, and PE was 0.11%. There was no significant different between DVT (p=0.88, 95% CI= -1.36% - 1.65%) or PE (p=0.45, 95% CI = -0.77% - 1.50%) between the control and study groups. The control group (no ASA) recorded an incidence of 0.62% DVT and 0.00% PE. As compared to the study group (ASA), which recorded an incidence of 0.47% DVT and 0.23% PE. The control group had significantly greater number of documented current smokers (8.68% vs 3.72%, p= 0.0003). The study group had a statistically significant higher mean age of subject (59.1 vs 57.7, p=0.0055), as well as more subjects undergoing revision RCR surgery (4.67% vs 1.86%, p= 0.021). Conclusion: Based on our study of 914 patients, ASA does not provide a clinically significant reduction in VTED rates in patients undergoing RCR. We conclude that the use of mechanical prophylaxis and early mobilization is a sufficient method of VTED prophylaxis in this low risk population.